Uslūb al-Iltifāt fī al-Juzʾ al-Akhīr min al-Qurʾān al-Karīm - Aqdi Rofiq Asnawi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
Iltifāt is one of the most important rhetorical devices in the Arabic language and one of the most frequently used stylistic features in the Holy Qur'an. It has been described as the "courage of the Arabic language" because it enhances discourse and captures the attention of both readers and listeners. The rhetorical beauty and subtle meanings embedded in iltifāt have led scholars of rhetoric, Qur'anic exegesis, and other disciplines to devote considerable attention to its study and analysis. Among these rhetorical subtleties are the various forms of iltifāt found in the last part of the Holy Qur'an. This study presents a brief discussion of the linguistic and technical definitions of iltifāt, together with an overview of its different forms. It then examines the Qur'anic verses in the final section of the Qur'an that demonstrate this rhetorical device, while presenting the interpretations of Qur'anic commentators concerning these verses. Finally, the study points out additional instances of iltifāt found in this section of the Qur'an without attempting to provide a complete statistical enumeration of all its occurrences.